Bones of betrayal eaudiobook Body farm series, book 4. - Bass, Jefferson (Body Farm, 2009)
World-renowned forensic anthropologist Dr. Bill Bass and acclaimed journalist Jon Jefferson have combined their talents on several New York Times best-sellers. A thrilling tale of suspense, Bones of Betrayal shows why Kathy Reichs praises Bass and Jefferson's "terrific forensic detail" and calls them "the real deal." "Southern-fried forensics. Nothing too fancy, but it does taste good going down."-Kirkus Reviews